Performance Evaluation of a Communication Protocol for Vital Signs Sensors Used for the Monitoring of Athletes - Kiokes, George; Vossou, Clio; Chatzistamatis, Panagiotis; Potirakis, Stelios M.; Vassiliadis, Savvas; Prekas, Kleanthis; Tuna, Gurkan; Gulez, Kayhan (HINDAWI PUBLISHING CORPORATION, 2014)
Monitoring vital signs in athletes, mainly during training, is of crucial importance for both the athlete and the coach, in order to avoid overtraining. Overtraining is an extreme state of fatigue that forces athletes to rest for several weeks having a negative impact on athlete's performance, health, and daily life. A wireless sensor network (WSN) combines embedded computing technology with communication technology in order to collect information of the network coverage area and send it to the observer. In this paper, we present results of system's performance evaluation for the IEEE 802.15.4 standard, including the physical (PHY) layer and media access control (MAC) sublayer, in order to collect and store large sets of athletes' data as well as providing results about network values such as end-to-end delay, load, and throughput captured from global and objects statistics.
Keywords: TRAINING LOAD; HEART-RATE; EXERCISE; Computer Science; Telecommunications